MS4A superfamily molecules in tumors, Alzheimer’s and autoimmune diseases - Luo, Xuejiao; Luo, Bin; Fei, Lei; Zhang, Qinggao; Liang, Xinyu; Chen, Yongwen; Zhou, Xueqin (Frontiers in Immunology, 2024)
MS4A (membrane-spanning 4-domain, subfamily A) molecules are categorized into tetraspanins, which possess four-transmembrane structures. To date, eighteen MS4A members have been identified in humans, whereas twenty-three different molecules have been identified in mice. MS4A proteins are selectively expressed on the surfaces of various immune cells, such as B cells (MS4A1), mast cells (MS4A2), macrophages (MS4A4A), Foxp3+CD4+ regulatory T cells (MS4A4B), and type 3 innate lymphoid cells (TMEM176A and TMEM176B). Early research confirmed that most MS4A molecules function as ion channels that regulate the transport of calcium ions. Recent studies have revealed that some MS4A proteins also function as chaperones that interact with various immune molecules, such as pattern recognition receptors and/or immunoglobulin receptors, to form immune complexes and transmit downstream signals, leading to cell activation, growth, and development. Evidence from preclinical animal models and human genetic studies suggests that the MS4A superfamily plays critical roles in the pathogenesis of various diseases, including cancer, infection, allergies, neurodegenerative diseases and autoimmune diseases. We review recent progress in this field and focus on elucidating the molecular mechanisms by which different MS4A molecules regulate the progression of tumors, Alzheimer’s disease, and autoimmune diseases. Therefore, in-depth research into MS4A superfamily members may clarify their ability to act as candidate biomarkers and therapeutic targets for these diseases. Eighteen distinct members of the MS4A (membrane-spanning four-domain subfamily A) superfamily of four-transmembrane proteins have been identified in humans, whereas the MS4A genes are translated into twenty-three different molecules in mice. These proteins are selectively expressed on the surface of various immune cells, such as B cells (MS4A1), macrophages (MS4A4A), mast cells (MS4A2), Foxp3+CD4+ regulatory T cells (MS4A4B), type 3 innate lymphoid cells (TMEM176A and TMEM176B) and colonic epithelial cells (MS4A12). Functionally, most MS4A molecules function as ion channels that regulate the flow of calcium ions [Ca2+] across cell membranes. Recent studies have revealed that some MS4A proteins also act as molecular chaperones and interact with various types of immune receptors, including pattern recognition receptors (PRRs) and immunoglobulin receptors (IgRs), to form signaling complexes, thereby modulating intracellular signaling and cellular activity. Evidence from preclinical animal models and human genetic studies suggests that MS4A proteins play critical roles in various diseases (2). Therefore, we reviewed the recent progress in understanding the role of the MS4A superfamily in diseases, particularly in elucidating its function as a candidate biomarker and therapeutic target for cancer.